2020
DOI: 10.1093/ofid/ofaa430
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of SARS-CoV-2 in Public Transportation Vehicles: A Case Study in Hunan Province, China

Abstract: Here we report a case study of a SARS-CoV-2 outbreak event during bus trips of an index patient in Hunan Province, China. This retrospective investigation suggests potential airborne transmission of SARS-CoV-2 and the possibility of superspreading events in certain close contact and closed space settings, which should be taken in to account when control strategies are planned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(96 citation statements)
references
References 8 publications
3
88
0
5
Order By: Relevance
“…The evidence available thus far is from Chinese studies, where airport or high-speed railway station travel was found to be associated to the speed of the infection spread ( 15 ). In particular, a strong association between travel by train to six major Chinese cities and the number of SARS-CoV-2 cases has been found ( 16 ); and an important SARS-CoV-2 outbreak in public transportation (bus) has also been reported ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…The evidence available thus far is from Chinese studies, where airport or high-speed railway station travel was found to be associated to the speed of the infection spread ( 15 ). In particular, a strong association between travel by train to six major Chinese cities and the number of SARS-CoV-2 cases has been found ( 16 ); and an important SARS-CoV-2 outbreak in public transportation (bus) has also been reported ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the first 2.5 hour leg on a larger bus, 7 of 48 riders were infected, including riders ~4.5 m away; on the second 1-hour leg on a smaller bus, 2 of 12 riders were infected [24] . (3) In February 2020, clusters of coronavirus transmission in aerobic dance exercise classes were found, in Korea, this time due to sick instructors [25] .…”
Section: Background and Motivationmentioning
confidence: 98%
“…Also in January 2020, an index patient in Wuhan, China took two different buses on a single trip. On the first 2.5 hour leg on a larger bus, 7 of 48 riders were infected, including riders ∼4.5 m away; on the second 1-hour leg on a smaller bus, 2 of 12 riders were infected [24].…”
Section: Background and Motivationmentioning
confidence: 99%
“…Of concern, a recent case study has identified buses resulting in a high transmission rate, R0, where 24 of 68 people became infected after riding one a bus with one infectious person (Shen et al 2020). Other studies describe a single person transmitted SARS-CoV-2 to 12 other individuals on two bus rides on a single day (Luo et al 2020). In addition, there have been transmission to almost 900 workers during the pandemic within a bus transportation organization, resulting in 8 deaths (Herguth and Hurley 2020).…”
Section: Introductionmentioning
confidence: 99%